Penilaian kritis artikel jurnal dalam lokakarya penelitian untuk pascasarjana: Studi kuasi-eksperimental - Rajendra Dnyandeo Jangle (Curricula: Journal of Curriculum Development, 2026)
The thesis serves as a prerequisite for every graduate program and a standard component of the graduate curriculum, designed to assess students’ mastery of specific coursework. This is a prospective study conducted during a three-day basic research workshop to evaluate the impact of various aspects of critical assessment instruction on students’ understanding. This article also reviews the available literature on critical evaluation for graduate students in the health sciences and provides guidance to help initiate the thesis process. To publish in a journal, one needs up-to-date information on various journals, citation indexes, and their impact factors. This article provides a current overview of bibliographic indexing agencies. Additionally, the critical evaluation of journal articles is explained in detail. The results of this study indicate that indexing information and the direct presentation of results have a significant impact on students’ understanding of critical evaluation. The inclusion and emphasis on journal indexing and information regarding the direct presentation of results in courses and workshops on research methodology for graduate students will represent a step forward in curriculum development.